Ozadje jugoslovanske velike noči - Kranjc, Janez (Pravnik, 2013)
The author examines what at first glance seems a naive enthusiasm of Slovenian politicians before the First World War for a union with South Slavs. Their likely intent was to achieve a fulfillment of language and other rights of Slovenian people. Slovenian politicians were convinced that the invo-cation of close ties with other Slavs increased their leverage in the do-mestic politics of the Monarchy. The main demand of Slovenian politics since the March revolution was related to the official use of Slovenian language. Despite clear legal guarantees it was not entirely carried out in practice.
Keywords: Austria-Hungary; Avstro-Ogrska; Balkan; Balkans; history; jezikovne pravice; Jugoslavija; mednarodni odnosi; narodnostno vprašanje; politična zgodovina; Rahten, Andrej: Jugoslovanska velika noč; Slovenci; Slovenes; Slovenia; Slovenija; Yugoslavia; zgodovina